Early melanoma invasivity correlates with gut fungal and bacterial profiles. (1st January 2022) - Vitali, F.; Colucci, R.; Di Paola, M.; Pindo, M.; De Filippo, C.; Moretti, S.; Cavalieri, D.
Summary: Background The microbiome is emerging as a crucial player of the immune checkpoint in cancer. Melanoma is a highly immunogenic tumour, and the composition of the gut microbiome has been correlated to prognosis and evolution of advanced melanoma and proposed as a biomarker for immune checkpoint therapy. Objectives We investigated the gut fungal and bacterial compositions in early‐stage melanoma and correlated microbial profiles with histopathological features. Methods Sequencing of bacterial 16S rRNA and the fungal internal transcribed spacer region was performed on faecal samples of patients with stage I and II melanoma, and healthy controls. A meta‐analysis with gut microbiota data from patients with metastatic melanoma was also carried out. Results We found a combination of gut fungal and bacterial profiles significantly discriminating patients with melanoma from controls. In patients with melanoma, we observed an abundance of Prevotella copri and yeasts belonging to the order Saccharomycetales. We found that the bacterial and fungal community correlated to melanoma invasiveness, whereas the specific fungal profile correlated to melanoma regression. Bacteroides was identified as general marker of immunogenicity, being shared by regressive and invasive melanoma. In addition, the bacterial communities in patients with stage I and II melanoma were different in structure and richer than those from patients with metastatic melanoma. Conclusions The composition of the gut microbiota in early‐stage melanoma changes along the gradient from in situ to invasive (and metastatic) melanoma. Changes in the microbiota and mycobiota are correlated to the histological features of early‐stage melanoma, and to the clinical course and response to immune therapies of advanced‐stage melanoma, through direct or indirect immunomodulation.